Can items derived from international literature be used in national quality of life instruments? A qualitative study conceptualising the EQ-HWB in China - Guangjie Zhang; Zhihao Yang; Nan Luo; Pei Wang; Jan Busschbach (SpringerOpen, 2024)
Abstract Introduction The EQ Health and Wellbeing (EQ-HWB) is a new questionnaire for measuring quality of life (QoL) from a broad perspective. The items of the EQ-HWB were derived based on a 'qualitative review' of literature, which reported primarily on Western studies. It can be argued that the QoL is a cultural-related concept and therefore people from China have a different understanding of the QoL. This study aimed to explore whether Chinese citizens could understand the EQ-HWB's candidate items and what they thought of those items. In doing so, we wanted to examine the face validity of the candidate items and explore if further cultural adaptation is necessary. Methods This research was part of the E-QALY project, in which 36 candidate items were selected for the EQ-HWB from a 97-item pool. In China, three interviewers investigated the face validity of these EQ-HWB candidate items in semi-structured qualitative face-to-face interviews. Respondents were invited to report 'problems' with regard to the interpretation of the items and these problems were grouped into themes. We explored to what extent those themes related to specific cultural aspects in China. We also classified the rates of reported problems for each item into three groups: 1) less than 20%, 2) from 20-50%, and 3) over 50%. Results For 17 items the rate of reported problems was less than 20%, 15 items fell into the second group (with 20 − 50%) and for 4 items the rate of problems reported was more than 50%. The thematic analysis revealed eight themes: ambiguous problems in the interpretation of 16 items; difficult to understand (11); contained a complex negative expression (10); examples used seemed inappropriate (7); misleading connotation in Chinese (2); long and complex (2); complex response options (1); and use of non-colloquial language (1). Discussion Our research shows that EQ-HWB candidate items require careful examination to make them more comprehensible. Most of the reported problem themes were generic problems related to the items, and only a few face validity issues appeared to relate to specific cultural aspects in China, even though most of the items were based on Western studies. Our findings are reassuring for the instrument's international application, especially in China.